Effect of Acute Iron Toxicity on Key Antioxidative Enzymes in Contrasting Rice (Oryza sativa L.) Cultivars of North-East India - Devi, Ayam Gangarani; Yadav, Gulab Singh; Devi, H. Lembisana; Ngachan, S.V. (International Journal of Bio-resource and Stress Management, 2023)
Iron toxicity is a nutritional disorder frequently occurring in lowland soils where rice is cultivated, due to the formation of excess ferrous iron in reduced soil condition. To contribute in understanding the mechanisms involved in response to excess iron, an investigation was carried out to determine the variation in symptom expression in leaves, tissue iron distribution and antioxidative enzyme activity in five rice cultivars viz., Kanatara, Katakchara, Maibetikala, Chinari and Lalgura of Northeast India. Hydroponically grown rice seedlings of these cultivars were exposed to a high Fe concentration (1000 mg l-1= 17.9 mM Fe2+), harvested after five weeks growth to study the antioxidative responses to excess iron stress. The iron accumulated in different plant tissues were analysed and the relatively tolerant cultivars showed higher retention of iron in root tissues, confirming that the dominant tolerance mechanisms in the tolerant cultivars were related to root based mechanism (i.e., iron exclusion). Higher superoxide dismutase and catalase activities were observed in cultivars Kanatara, Katakchara, Chinari and Lalgura. Conversely, cultivar Maibetikala showed significant reductions in superoxide dismutase and catalase activities. In response to high iron level in growth medium, cultivar Maibetikala maintained higher ascorbic peroxidase and glutathione reductase activities. Results of the study reveal that the rice cultivars differ in their response to iron toxicity and the tolerance attributes largely depend on the enhancement of antioxidative enzymes, suggesting that antioxidative enzymes has a significant role in protecting the plants against oxidative damage under iron toxic conditions.